Mangrove biomass productivity and sediment carbon storage assessment at selected sites in Mauritius: the effect of tidal inundation, forest age and mineral availability - M D D Doodee; S D D V Rughooputh; S Jawaheer (Environmental Research Communications)
Carbon dioxide is the most abundant anthropogenic greenhouse gas released in the environment and is considered as one of the main drivers of global warming and ensuing climate change. Mangals, recognised as key ‘blue carbon’ ecosystems, are amongst the world’s most carbon-dense ecosystems and can sequester a considerable amount of carbon through biological carbon sequestration in their biomass and soils. In this work, five Rhizophora mucronata natural and planted forests in Mauritius were studied with the aims at evaluating the carbon storage potential and the effect of tidal inundation, forest age, and mineral availability on biomass productivity and sediment carbon storage. Using 25m x 25m quadrats and a simple random sampling technique, plant height and diameter at breast height (DBH) were measured in situ with the GLOBE Observer application (The Globe Program, NASA-sponsored) and a measuring tape, respectively. The rate of canopy coverage over the past twenty years was assessed using historical Landsat 7 and 8 images available on Google Earth Pro. Rhizophora allometric equations were used to estimate the above-ground biomass (AGB), below-ground biomass (BGB), and total biomass (TB). Total organic carbon (TOC), sediment carbon storage, and all essential nutrients for plant growth were analysed using standard methods. Soil texture was determined using granulometric analysis. Our findings show that in both natural and planted forests, the zones that were more inundated were first established. However, tree and sapling density, as well as biomass, were negatively correlated with sodium (density: r = −0.830; AGB: r = −0.880). Positive correlations between AGB and nitrate nitrogen (NO _3 -N) (r = 0.686), ammonium nitrogen (NH _4 -N) (r = 0.706), phosphate (r = 0.618), and manganese (r = 0.776) suggest that these minerals were limiting factors. Nevertheless, the combination of forest age and salinity was found to play key roles on the AGB and therefore on total organic carbon (TOC), which is linked to materials originating from the mangroves. High correlations of TOC with NH _4 -N (r = 0.822) and magnesium (r = 0.831) indicate the greater availability of these essential nutrients in older forests. It is noteworthy that the Ferney forest with a relatively lower salinity (5–15 ppt) and the only forest that had already reached a steady state in 2010, had a relatively much higher AGB (326.2 ± 26.3 t ha ^−1 ) than the global average for Rhizophora mucronata (94.8 t ha ^−1 ), let alone Rhizophora spp. (281 t ha ^−1 ). The TOC registered at Ferney (47.34%) was also higher than the global values reported (2.00 ± 2.20% to 40.00 ± 2.20%).